Fostering Diversity Values Through Learning The History of The National Movement in Senior High Schools - Muslim; Warto; Djono (International Journal of Social Learning (IJSL), 2021)
This study aims to find out how to foster the value of diversity through learning the history of the national movement in Senior High Schools. This study uses a qualitative method, with a single case study strategy. This research was conducted at the National Senior High School. The data validity was used triangulation. Data were collected through interviews, a document study, and observation. The data analysis technique used the interactive model of Miles and Huberman analysis. The results of the study: 1) Planning, the history teacher has prepared and compiled a lesson plan which contains the values of diversity. 2) Implementation, history teachers teach material about national movement figures, use discussion methods, train students to respect friends who are different from them such as differences in religion, ethnicity, race, ethnicity, social system, and culture. 3) Evaluation, history teachers have used the principle of overall evaluation and continuity and have been implemented properly by history teachers. 4) Barriers because currently learning is carried out online, so teachers cannot see what students are doing as it is when learning is done in class. In the end, this study showed that after the obstacles were overcome, the students' diversity values increased.